Electrophysiological testing is correlated with myasthenia gravis severity. Issue 3 (23rd March 2017) - Abraham, Alon; Breiner, Ari; Barnett, Carolina; Katzberg, Hans D.; Lovblom, Leif E.; RT, Mylan Ngo; Bril, Vera
ABSTRACT: Introduction: Electrophysiological studies play an important role in the diagnosis of myasthenia gravis (MG). The objectives of this study was to explore the correlation of jitter and decrement with various clinical symptoms and signs and disease severity. Methods: We performed a retrospective chart review of 75 MG patients who attended the neuromuscular clinic from April 2013 to May 2014. We compared clinical characteristics between patients with high jitter (>100 µs) and decrement (>10%), and patients with lower values to explore the correlations and optimal thresholds of jitter and decrement for different clinical features. Results: High jitter and decrement values were associated with more severe disease, manifested by more frequent symptomatic bulbar and limb muscle weakness, more frequent ocular and limb muscle weakness on examination, higher quantitative MG score, and generalized disease. Conclusions: The yield of the electrophysiological assessment in MG extends beyond disease diagnosis and correlates with disease severity and the presence of generalized disease. Muscle Nerve 56 : 445–448, 2017